The Study of Spatial-Time-Frequency Correlation Properties of 5G Channel Modeling of MIMO-OFDM System - Nguyen, Thu Nga; Nguyen, Tien Hoa; Ta, Phuong Nam (Old Journal, 2020)
The fifth generation (5G) mobile communication systems will have the speed more 100 times compared to the 4G and with the aim is to provide every propagation environment for every destination. Multiple-input multiple-output (MIMO) communication is the important technology researched for 5G systems. This paper studies the correlation properties of 5G channel modeling in MIMO system such as auto-correlation functions of time and frequency, as well as the spatial cross-correlation function. The scenarios UMi, RMa and indoor cells are investigated at 6 GHz frequency band in non-line of sight (NLOS) case. We calculate the spatial-temporal-frequency correlation functions of the 5G MIMO channel to estimate the system level in physical layer. From that, we conclude the minimum correlation values are depended on the distance of antenna elements in each transmitter and receiver side. We also identify the offset in time and frequency domains to identify the stability of the signal in a certain range.